(untitled) (Iranian Journal of Kidney Diseases, 2015)
Introduction. Observing the effects of high-volume hemofiltration (HVHF) treatment on the monocytes apoptosis, antigen presentation, and secretion function, this study investigated the mechanism of HVHF effect on immunity homeostasis in multiple organ dysfunction syndrome (MODS) in an animal model. Materials and Methods. Lipopolysaccharides were administered in 12 Beagle dogs in order to induce MODS. Six dogs were randomly assigned to receive HVHF treatment for 12 hours (HVHF group) and the rest did not receive any treatment (the MODS group). The expression of DLA-DR, apoptosis, and cytokine levels were measured at 7 time points: normal condition (T1), after operation (T2), and zero, 3, 6, 9, and 12 hours after endotoxin injection (T3 to T7, respectively). Results. Apoptosis of CD14+ mononuclear cell increased in early and late stages gradually in the MODS group and began to decline gradually after the HVHF treatment. There was a significant difference between the two groups at time points T2 to T7 (P < .01). After HVHF, the impaired expression of dog leukocyte antigen-DR showed an improvement trend in the HVHF group, which was significant better at T5 and T7 than that in the MODS group (P < .05). Interleukin-4 secretion increased significantly with HVHF and was significantly higher at time points T4 to T7 as compared with the MODS group (P < .01). Conclusions. High-volume hemofiltration can alleviate the mononuclear cell apoptosis, improve antigen-presenting function and secretion function, inhibit the release of inflammatory factors, and maintain immune homeostasis, and consequently alleviate symptoms of MODS effectively.